Peran Pendidikan PAI dalam Meningkatkan Kesadaran Anak dan Remaja terhadap Perubahan Iklim - Himmatut Thoyibah; Akbar Maulana Fakhruqi (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
The issue of climate change is a global challenge that has a broad impact on human life, including the younger generation as the future heirs. From an Islamic perspective, the environment is not merely a biological living space, but a divine mandate that must be protected and managed responsibly by humans as caliphs on earth. This study uses a qualitative method with a library research approach to analyze environmental values ​​in Islamic teachings and their relevance in Islamic Religious Education (PAI) learning. Research data sources include the Qur'an, hadith, academic books, scientific journals, and publications discussing Islamic ecology and environmental education. The results show that the concept of the caliph, the prohibition of fasād, the principle of mīzān, and the anti-isrāf attitude provide a strong theological foundation for building students' ecological awareness. These values ​​can be systematically integrated into materials on faith, morals, jurisprudence, and practice-based learning through ecological activities in schools. PAI learning functions not only as a transfer of religious knowledge, but also as an instrument for forming ecological character based on Islamic spirituality. Thus, Islamic Religious Education has the potential to be an educational strategy for developing a generation that cares about the environment, behaves in an environmentally friendly manner, and is able to contribute to sustainable climate change mitigation from a moral, social, and spiritual perspective.